Abortion before birth control : the politics of reproduction in postwar Japan - Norgren, Christiana A. E., 1970- (Studies of the East Asian Institute., 2001)
Why has postwar Japanese abortion policy been relatively progressive, while contraception policy has been relatively conservative? The Japanese government legalized abortion in 1948 but did not approve the pill until 1999. In this carefully researched study, Tiana Norgren argues that these contradictory policies flowed from very different historical circumstances and interest group configurations. Doctors and family planners used a small window of opportunity during the Occupation to legalize abortion, and afterwards, doctors and women battled religious groups to uphold the law. The pill, on the other hand, first appeared at an inauspicious moment in history. Until circumstances began to change in the mid-1980s, the pharmaceutical industry was the pill's lone champion: doctors, midwives, family planners, and women all opposed the pill as a potential threat to their livelihoods, abortion rights, and women's health. Clearly written and interwoven with often surprising facts about Japanese history and politics, Norgren's book fills vital gaps in the cross-national literature on the politics of reproduction, a subject that has received more attention in the European and American contexts. Abortion Before Birth Control will be a valuable resource for those interested in abortion and contraception policies, gender studies, modern Japanese history, political science, and public policy.